Thermal enhancement of ethylene glycol base material with hybrid nanofluid for oblique stagnation point slip flow - Lioua Kolsi; A. Abbasi; Umar F. Alqsair; W. Farooq; Mohamed Omri; Sami Ullah Khan (Case Studies in Thermal Engineering, 2021)
The hybrid nanofluids are more effective and stable to improve the thermal activities of many base liquids. With eminent thermal consequences, the hybrid nanofluids are preferred as compared to simple nanofluids which present the applications in industrial and engineering sectors. This mathematical model described in the thermal applications of hybrid nanofluids due to a non-orthogonal stagnation point addressed over a stretching cylinder. The hybrid nanofluid constrains the multi-walled carbon nanotubes (MWCNT) and single-walled carbon nanotubes (SWCNT). The Ethylene glycol is considered as base fluid. The heat generation features and slip constraints are also introduced to modify the thermal model. The assumed flow is observed due to stretched cylinder with applications of oblique stagnation point flow. The phenomenon of oblique stagnation point flow pattern is quite interesting. The similarity transformations are used to reduce the governing system of partial differential equations into system of ordinary differential equations. The results are exhibited in the present analysis by using efficient and second order accurate numerical scheme Keller box method. The graphical results for different features of flow and heat transfer are presented and discussed. It is observed that the tangential velocity declines with the velocity ratio parameter which is more progressive when the slip features are dominant. An increase in the solid volume fraction results a lower change in temperature profile. With increase in the curvature parameter, the heat transfer rate improved for non-convective stretching cylinder while the opposite observations are claimed for convective stretched cylinder.